EFEKTIVITAS PENYULUHAN KESEHATAN TENTANG PENCEGAHAN KANKER SERVIKS DENGAN MEDIA LEMBAR BALIK TERHADAP MOTIVASI WANITA USIA SUBUR DALAM DETEKSI DINI KANKER SERVIKS - Prithania Dwiza Renanda; Sri Utami; Bayhakki Bayhakki (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Cervical cancer is one of the causes of death for woman in the world, including Indonesia. Cervical cancer is a malignant tumor that affects the surface layer (epithelium) and the cervix. The study aims to determine the effectiveness of health counseling on cervical cancer prevention with flipchart on the motivation of fertile age woman in early detection of cervical cancer. This study used a pre-experimental design, one group pre-test pos-test method. This research was conducted in the village of Labuh Baru Timur, Payung Sekaki sub district with 34 respondents as the samples and used purposive sampling technique based on inclusion criteria. The measuring instrument used was a questionnaire that has been tested for validity and reliability. The analysis used was univariate analysis and bivariate analysis with the dependent t test an the Wilcoxon test. The test results of the dependent sample t test showed that p value was 0,000, wich means p value < 0,05. This means that H0 is rejected, it can be concluded that health education about cervical cancer prevention is effective in increasing the motivation of fertile age woman to prevent cervical cancer in early detection of cervical cancer.Keywords: Cervical Cancer; Flipchart; Health Counseling; Motivation.